Corruption, Growth, and Public Finances - Tanzi, Vito (IMF Working Papers; Working Paper ;, 2000)
The paper discusses some channels through which corruption affects growth such as the impact of corruption on enterprises, on the allocation of talent, and on investment. It also discusses the impact of corruption on some aspects of public finance.